Low bone mineral density in pre-menopausal women one year after gastric bypass - Silva, Thalane Souza Santos; Curvello-Silva, Karine Lima; Palhares-de-Oliveira, Nataly Azenate; Bastos, Isis Henriques de Almeida; Sousa, Cláudia Daltro de; Daltro, Carla (Revista de Ciências Médicas e Biológicas, 2022)
Introduction: nutritional deficiencies, hormonal changes and severe weight loss after Roux-en-Y Gastric Bypass (RYGB) can promote changes in bone metabolism which may lead to a reduction in bone mineral density (BMD). Objective: to investigate the prevalence of osteopenia/osteoporosis and factors associated with BMD in pre-menopausal women who underwent RYGB. Methodology: a cross-sectional study conducted with secondary data of patients followed-up in a specialized center for obesity treatment. Variables studied: biochemical and anthropometric data, body composition by multifrequency bioimpedance and BMD of the lumbar spine (LS), total femur (TF) and femur neck (FN) by dual-energy X-ray absorptiometry. For statistical analysis, the SPSS® software and a 5% significance level were utilized. Results: seventy-two (72) pre-menopausal women were evaluated. Mean age, BMI and mean post-surgery time was 38.7±6.5 years, 25.8±2.5 kg/m² and 13.1±1.7 months, respectively. The prevalence of osteopenia in at least one of the densitometry sites was 13.9%, with LS being the most frequent site. A lower LS BMD was associated with greater weight loss, higher percentage of body fat before surgery and lower post-surgery serum vitamin D levels. There was a positive correlation between skeletal muscle mass index adjusted for height in the pre-surgery period and LS BMD (r=0.361; p=0.010) and TF (r=0.404; p=0.004). Conclusion: a relevant prevalence of osteopenia was detected in pre-menopausal women after RYGB, mainly in the LS.